Pharmaceutical Removal with Photocatalytically Active Nanocomposite Membranes - Marin Popović; Silvia Morović; Marin Kovačić; Krešimir Košutić (Membranes)
The advancement of pharmaceutical science has resulted in the development of numerous tailor-made compounds, i.e., pharmaceuticals, tuned for specific drug targets. These compounds are often characterized by their low biodegradability and are commonly excreted to a certain extent unchanged from the human body. Due to their low biodegradability, these compounds represent a significant challenge to wastewater treatment plants. Often, these compounds end up in effluents in the environment. With the advancement of membrane technologies and advanced oxidation processes, photocatalysis in particular, a synergistic approach between the two was recognized and embraced. These hybrid advanced water treatment processes are the focus of this review, specifically the removal of pharmaceuticals from water using a combination of a photocatalyst and pressure membrane process, such as reverse osmosis or nanofiltration employing photocatalytic nanocomposite membranes.